Influence of sinter grate suction pressure (flame front speed) on microstructure, productivity and quality of iron ore sinter. (July 2014) - Umadevi, T.; Brahmacharyulu, A.; Sah, R.; Mahapatra, P. C.
<x content-type="archive" xml:space="preserve">Abstract</x> From a sinter production point of view, it is important to optimise the sintering process with regard to both sinter quality and production rate. In sintering, airflow rate within the sinter bed decides the production rate and its physical and metallurgical properties. To study the influence of airflow rate (flame front speed) on sinter production and sinter quality, pot grate sintering experiments were conducted at sinter grate suction pressures ranging from 900 to 1700 mm water column over the sinter bed. During sintering, time–temperature data were recorded, and mineralogical studies were carried out. This study reveals that increase in sinter grate suction pressure through the sinter bed from 900 to 1700 mm water column significantly improved the sinter productivity from 34·37 to 48·90 t/m2/day; however, the physical and metallurgical properties of the sinter at higher suction pressure were not optimum with respect to blast furnace requirements. The maximum sinter productivity with desired physical and metallurgical properties was obtained at suction pressure 1300 mm water column. At this pressure, improvement in sinter quality was due to optimum firing temperature and enough retention time available for formation of mineral phases. At an airflow rate 1300 mm water column, sinter productivity was 41·0 t/m2/day, sinter strength (TI) was 73·10%, reduction degradation index was 25·0 and reducibility was 71·50%.